1992
DOI: 10.1002/ijc.2910510315
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzable tannins: Potent inhibitors of hydroperoxide production and tumor promotion in mouse skin treated with 12‐O‐tetradecanoylphorbol‐13‐acetate in vivo

Abstract: The anti-oxidant and the anti-tumor-promotion activities of several hydrolyzable tannins (HTs), including a commercial tannic-acid (TA) mixture, were examined in mouse skin treated with 12-O-tetradecanoylphorbol-13-acetate (TPA) in vivo. A single application of TPA gradually increases the hydroperoxide (HPx)-producing activity of the epidermis, which is maximally stimulated at 3 days and returns to control levels at 9 days. Pre-treatments with TA and ellagic acid (EA) strongly inhibit, in a dose-dependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…For example, TA has been reported to have antioxidant and anti-inflammatory properties (76,77), and we went on to determine whether the compound impacted neuroinflammation, an important AD pathoetiologic hallmark (53,54), in PSAPP mice. Interestingly, oral TA treatment reduced microgliosis, astrocytosis, and expression of the proinflammatory cytokines TNF-␣ and IL-1␤ in PSAPP mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TA has been reported to have antioxidant and anti-inflammatory properties (76,77), and we went on to determine whether the compound impacted neuroinflammation, an important AD pathoetiologic hallmark (53,54), in PSAPP mice. Interestingly, oral TA treatment reduced microgliosis, astrocytosis, and expression of the proinflammatory cytokines TNF-␣ and IL-1␤ in PSAPP mice.…”
Section: Discussionmentioning
confidence: 99%
“…As already mentioned several classes of plant-derived antioxidant polyphenols also exhibit oxidative DNA degradation properties particularly in the presence of transition metal ions such as copper. Evidence in the literature suggests that antioxidant properties of these polyphenols may not fully account for their anticancer effects [27]. Further, we have previously shown that the polyphenol gallic acid is highly efficient in DNA degradation as compared with syringic acid (where two of the hydroxyl groups of gallic acid are modified) [28].…”
Section: Effect Of Pre-incubation Of Lymphocytes With Resveratrol Ormentioning
confidence: 99%
“…The use of vegetable tannins such as quebracho, mimosa, gall-nut, chestnut and valonia as a biocide in leather soaking process was also studied [18] owing to their antimicrobial and antiseptic properties [19]. Tannic acid, which is a commercially important hydrolysable gallotannin, has also got a great deal of attention as an antimicrobial agent due to its antimicrobial, antimutagenic, anticarcinogenic and antioxidant properties [1, 3,4,10,22,23,31,35,37,41,44]. Tannic acid is present in a variety of fruits and vegetables including tea, cocoa, beans, grapes, strawberry, persimmon, especially the bark of the oak species, sumac and myrobalan [1, 11,40] and also categorized as a 'generally recognized as safe' (GRAS) food additive [1].…”
Section: Introductionmentioning
confidence: 99%